2008
DOI: 10.3349/ymj.2008.49.1.58
|View full text |Cite
|
Sign up to set email alerts
|

Rarity of TLR4 Asp299Gly and Thr399Ile Polymorphisms in the Korean Population

Abstract: PurposeActivation of the innate immune system and chronic low-grade inflammation are thought to be involved in the pathogenesis of atherosclerosis and also thought to be associated with type 2 diabetes and its complications. As a receptor for bacterial lipopolysaccharide and heat-shock proteins, Toll-like receptor 4 (TLR4) is one of the central regulators of the immune response. Recent studies have reported an association between TLR4 polymorphisms and diabetes and its complications in Caucasian populations.Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
30
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 33 publications
6
30
0
Order By: Relevance
“…To date, several single nucleotide polymorphisms (SNPs) have been identified in the human TLR4 gene (Raby et al, 2002;Kolz et al, 2008;Arora et al, 2011;Jiang et al, 2013), such as Asp299Gly (Rudofsky et al, 2004;Kim et al, 2008;Buraczynska et al, 2009;Arora et al, 2011;Maldonado-Bernal et al, 2011;Jiang et al, 2013) and Thr399Ile (Rudofsky et al, 2004;Kim et al, 2008;Kolz et al, 2008;Buraczynska et al, 2009;Maldonado-Bernal et al, 2011;Jiang et al, 2013). Furthermore, several studies proved that the TLR4 gene variants were associated with susceptibility to T2DM (Rudofsky et al, 2004;Kim et al, 2008;Kolz et al, 2008;Buraczynska et al, 2009;Arora et al, 2011;Maldonado-Bernal et al, 2011;Jiang et al, 2013). However, the data from these studies are inconsistent, and the exact mechanism is poorly understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, several single nucleotide polymorphisms (SNPs) have been identified in the human TLR4 gene (Raby et al, 2002;Kolz et al, 2008;Arora et al, 2011;Jiang et al, 2013), such as Asp299Gly (Rudofsky et al, 2004;Kim et al, 2008;Buraczynska et al, 2009;Arora et al, 2011;Maldonado-Bernal et al, 2011;Jiang et al, 2013) and Thr399Ile (Rudofsky et al, 2004;Kim et al, 2008;Kolz et al, 2008;Buraczynska et al, 2009;Maldonado-Bernal et al, 2011;Jiang et al, 2013). Furthermore, several studies proved that the TLR4 gene variants were associated with susceptibility to T2DM (Rudofsky et al, 2004;Kim et al, 2008;Kolz et al, 2008;Buraczynska et al, 2009;Arora et al, 2011;Maldonado-Bernal et al, 2011;Jiang et al, 2013). However, the data from these studies are inconsistent, and the exact mechanism is poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, studies reported that there is a very high T2DM incidence in China where diabetes has become a major public health problem (Yang et al, 2010), with approximately 92.4 million adults with the disease and 148.2 million with prediabetes (Jiang et al, 2013). A large number of previous studies have shown that the human Toll-like receptor 4 (TLR4) is potentially an important gene influencing the susceptibility to T2DM (Illig et al, 2003;Rudofsky et al, 2004;Creely et al, 2007;Kim et al, 2008;Buraczynska et al, 2009;Arora et al, 2011;Maldonado-Bernal et al, 2011;Jiang et al, 2013). To date, several single nucleotide polymorphisms (SNPs) have been identified in the human TLR4 gene (Raby et al, 2002;Kolz et al, 2008;Arora et al, 2011;Jiang et al, 2013), such as Asp299Gly (Rudofsky et al, 2004;Kim et al, 2008;Buraczynska et al, 2009;Arora et al, 2011;Maldonado-Bernal et al, 2011;Jiang et al, 2013) and Thr399Ile (Rudofsky et al, 2004;Kim et al, 2008;Kolz et al, 2008;Buraczynska et al, 2009;Maldonado-Bernal et al, 2011;Jiang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19] The TLR4 Asp299Gly polymorphism, in particular, is the highest in African Americans, while in a western Iran population, the highest incidence for a mutation was found for the TLR4 Thr399Ile polymorphism, which is in, contrast, very rare in Asian populations, such as those in Japan and South Korea. 20,21 Carriers of the Thr399Ile TLR4 gene mutation have a significantly increased risk of developing GVHD, 42% versus 15% of non-affected patients, whereas transplant-related mortality, overall survival rate and the incidence of infectious complications are not influenced by the mutated gene. 22 Histopathological changes in the small intestine are more severe in TLR4-mutant host GVHD recipients than those in TLR4-intact host GVHD recipients at 14 days after GVHD development, 23 but the studies reporting these results did not clearly demonstrate the role of TLR4 in the HSCT-related pathogenesis of GVHD.…”
Section: Introductionmentioning
confidence: 99%
“…Our literature search identified four studies that evaluated the Asp299Gly and Thr399Ile polymorphisms in Asian populations, but they could not be included in the present meta-analysis because only the ancestral genotypes were found [39][40][41][42]. The lower frequency of the minor alleles of these TLR4 polymorphisms in Asians will require larger sample sizes to detect any statistically significant association with T2DM.…”
Section: Citationmentioning
confidence: 92%